INFLUENCE OF MENTORING ON BUSINESS EDUCATORS’ DOMAINS OF ORGANIZATIONAL COMMITMENT WITH MODERATING ROLE OF GENDER - OJEAGA, IBHADE JOY; OSAGUMWENRO, IGBINOGHODUA MOSES (Sokoto Educational Review, 2025)
Many Business educators seem to display negative attitudes such as lateness to work, meetings and classes, lateness in preparation and submission of students’ results. More worrisome is the fact that many of these educators quit lecturing jobs frequently in search for greener pastures in financial institutions, politics, and multi-national companies. To this end, this study investigated how mentoring influenced the domains of organizational commitment of business educators in Edo and Delta States, Nigeria. Three research questions were answered and three null hypotheses were tested in the course of the study. The descriptive survey design was used with a census sample of 211 business educators. The instrument was a 4 point rating scale of 24 items and was validated by three experts in the field of Business Education. Reliability of instrument was determined by administering the instrument to 20 business educators who were not part of the sample once and Cronbach Alpha statistics was used to determine the statistical value which yielded a reliability co-efficient of 0.87. Answering of the research questions was carried out using Mean and Standard Deviation while analysis of the null hypotheses was carried out using t-test at 0.05 level of significance. Results showed that mentoring influenced the three domains of business educators’ organizational commitment in the period under study. Hypotheses testing showed that there was no significant difference in the influence of mentoring on the organizational commitment of male and female business educators. Therefore, it was recommended that authorities in charge of Business Education in Edo and Delta States should ensure that there is a formal structure to continue to foster mentoring among the educators through departmental well-designed mentoring programmes with clear expected outcomes. DOI: https://doie.org/10.0301/SER.2025840277